2000
DOI: 10.1590/s0102-76382000000200005
|View full text |Cite
|
Sign up to set email alerts
|

Técnica cirúrgica simplificada pode ser eficaz no tratamento da fibrilação atrial crônica secundária a lesão valvar mitral?

Abstract: (1)(2)(3) . Foi descrita por William Harvey como "movimento atrial ondulante", caracterizando-se pelo ritmo irregular e anárquico do coração, há mais de 300 anos (4) . Sua prevalência aumenta dramaticamente com a idade, resultando, nos pacientes idosos, em substancial morbidade (5) . Na FA ocorre um aumento de três a cinco vezes no risco de acidente vascular cerebral isquêmico, sendo esse maior quando existe concomitância de valvopatia (6) . A importância no manejo de FA na população geral reside no fato de q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
9
0
4
Order By: Relevance
“…KALIL et al [14] presented a study that demonstrated similar results in respect to reversal to sinusal rhythm among patients operated by the simplified technique for left atrium isolation and those operated by the classic Cox-Maze III technique.…”
Section: Hospital Morbid-mortalitymentioning
confidence: 90%
“…KALIL et al [14] presented a study that demonstrated similar results in respect to reversal to sinusal rhythm among patients operated by the simplified technique for left atrium isolation and those operated by the classic Cox-Maze III technique.…”
Section: Hospital Morbid-mortalitymentioning
confidence: 90%
“…KALIL et al (62) mostraram, baseados em evidên-cias de serem as veias pulmonares a origem da maioria da fibrilação atrial e devido à complexidade do procedimento do labirinto, técnica cirúrgica simplificada, realizando incisão única, ao redor dos quatro óstios das veias pulmonares, acrescida de outra, unindo aquela incisão ao anel valvar mitral posterior.…”
Section: Comentáriosunclassified
“…Kalil et al [19] published a study in which they performed only the isolation of pulmonary vein ostia, reaching 86% of sinus rhythm after a 1-month follow-up. These results were similar to those achieved in the present study, in which only the left atrium was addressed, with 100% of AF reversion after surgery and 77.27% at six months.…”
Section: Discussionmentioning
confidence: 99%